Fatty Acid Composition of a Maternal Diet and Erythrocyte Phospholipid Status in Latvian Pregnant Women - Ksenija Nikolajeva; Olga Aizbalte; Anna Piskurjova; Roberta Rezgale; Vinita Cauce; Dzintars Začs; Laila Meija (Medicina, 2023)
Background and Objectives: Dietary fats are essential for maternal and fetal health. Fatty acids (FAs) in erythrocytes characterize the FA profile, which is influenced by diet and other factors. The aim of this study was to evaluate the association between the main FAs in erythrocyte membrane phospholipids and their influencing factors—dietary fat and supplement intake and lifestyle factors—in Latvian pregnant women. Materials and Methods: This cross-sectional study included 236 pregnant and postpartum women. The data were collected from medical documentation, a food frequency questionnaire, and a questionnaire on demographic, lifestyle, health status, and nutritional habits in outpatient clinics and maternity departments. FAs in erythrocyte membrane phospholipids were determined using gas chromatography. Results: Correlations were found between dietary SFAs and erythrocyte SFAs (r = −0.140, p = 0.032) and PUFAs (r = 0.167, p = 0.01) and between dietary PUFAs and erythrocyte MUFAs (r = −0.143, p = 0.028). Dietary SFAs, MUFAs, and PUFAs positively correlated with the studied n-3 and n-6 FAs in erythrocytes. Vitamin D correlated positively with MUFA and negatively with total PUFA and AA in erythrocytes. There was a negative correlation between dietary vitamin A and linoleic acid in erythrocytes. Physical activity negatively correlated with erythrocyte MUFAs and positively with erythrocyte PUFAs. Alcohol consumption positively correlated with erythrocyte SFAs and negatively with erythrocyte PUFAs. Conclusions: There are indications that some dietary FAs may be correlated with erythrocyte FAs. Possible influencing factors for this association are alcohol, physical activity, vitamin D, and vitamin A.